PENERAPAN PEMBELAJARAN TEMATIK KELAS RENDAH DI MI MIFTAHUL ULUM GENDOL SUKOREJO PASURUAN - Wiwik Nur Hayati; Ika Ratih Sulistiani; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
Abstract The purpose of this study was to describe the application of low class thematic learning at MI Miftahul Ulum Gendol Sukorejo Pasuruan. The approach used is a quality counselor with a type of case study research. Data collection is done by means of observations, interviews and documentation. The analysis of the data used includes: a) data reduction, b) displacement of data, 3) withdrawal of conclusions and verification. The results of the study show that the application of thematic learning is good enough. This can be seen in the application of thematic learning in accordance with those in thematic learning, such as the teacher has designed learning plans, provides learning media, in the core activities the teacher has used a scientific approach, but in the implementation of thematic learning the teacher has not fully understood thematic learning. Keywords: Thematic Learning, Low Class